RESEÑA de : Granada, Miguel Ángel ; Ríus, Rosa ; Schiavo, Piero (eds.). Filósofos,Filosofía y filosofías en la Encylopèdie de Diderot y d’Alembert : actas del Congreso Internacional sobre la Encyclopèdie, Barcelona 16-17 Octubre 2008. Barcelona : Universidad de Barcelona, 2009. - Eloy, Rada García (ENDOXA, 2010)
-